A model system for the investigation of rare earth collector interaction. (October 2016) - Cui, Jianlan; Hope, Gregory A.
Graphical abstract: Magnetic AFM scan for cerium carbonate thin film on calcite; Scan size: 15 μm × 15 μm. Cerium carbonate generally formed triangle shaped particles sized from 0.5 μm × 0.5 μm × 0.5 μm to 1 μm × 1 μm × 1 μm on calcite. Highlights: A cerium carbonate thin film has been synthesized for interaction studies. The study established the utility of magnetic AFM for surface investigation. The adsorption studies demonstrated that hydroxamate is selective to Ce over Ca. Abstract: A model system was used to investigate the interaction between carbonate mineral and octanohydroxamate collector. Bastnaesite (Ce) is the most important rare earth mineral that has been the dominant the rare earth source since 1960s. In this study, a synthetic cerium carbonate thin film on a calcite (most common gangue mineral occurring with rare earth minerals) substrate was formed for a surface interaction investigation. The cerium carbonate thin film system was characterized using Raman spectroscopy, atomic force microscopy and magnetic atomic force microscopy. An adsorption study between the model compound and hydroxamate was also conducted. The study established the utility of using atomic force microscopy and magnetic atomic force microscopy to investigate the mineral surface interaction. Weak adsorption on the thin film surface was observed after 5 h and 24 h of conditioning and the hydroxamate adsorption became evident after 72 h of conditioning. The adsorption studies for cerium carbonate and calcite also demonstrated that hydroxamate is selective to Ce over Ca.